2018
DOI: 10.1016/j.jaci.2017.10.038
|View full text |Cite|
|
Sign up to set email alerts
|

Autophagy deficiency in myeloid cells exacerbates eosinophilic inflammation in chronic rhinosinusitis

Abstract: Our results suggest that impaired autophagy in myeloid cells, particularly macrophages, has a causal role in eosinophilic inflammation and ECRS pathogenesis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
53
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(67 citation statements)
references
References 65 publications
4
53
0
Order By: Relevance
“…65 In addition, impaired autophagy in myeloid cells was reported to aggravate eosinophilia, epithelial hyperplasia, and mucosal thickening in mice with eosinophilic CRS. 66 Decreased expression of antimicrobial S100 proteins in the epithelium of patients with CRS might lead to diminished innate immune responses and barrier function. 67,68 …”
Section: Epithelial Barrier Defect and Reduced Innate Immunity In Crsmentioning
confidence: 99%
“…65 In addition, impaired autophagy in myeloid cells was reported to aggravate eosinophilia, epithelial hyperplasia, and mucosal thickening in mice with eosinophilic CRS. 66 Decreased expression of antimicrobial S100 proteins in the epithelium of patients with CRS might lead to diminished innate immune responses and barrier function. 67,68 …”
Section: Epithelial Barrier Defect and Reduced Innate Immunity In Crsmentioning
confidence: 99%
“…The same study showed that BMMC lacking Atg7 or 12 have normal granule formation, but defective IgE-mediated degranulation, demonstrating the importance of autophagic machinery in granule movement and release. Furthermore, dysregulation of autophagy in mast cells has been shown in various disease states such as systemic sclerosis, chronic rhinosinusitis, and asthma ( 48 50 ). Overall, research on mast cell survival, apoptosis, and autophagy pathways suggests that these pathways are important for both maintenance and function in both health and disease.…”
Section: Mast Cell Growth Survival and Apoptosismentioning
confidence: 99%
“…The JACI advances in 2018 examined both the factors leading to tissue eosinophilia and the effect of eosinophils on the inflammatory process itself. In a novel study examining the role of the prostaglandin pathway in chronic rhinosinusitis (CRS), Choi et al 1 deleted the autophagy-related gene Atg7 in the myeloid lineage of mice challenged with a mixture of Aspergillus species protease and ovalbumin to induce CRS. 1 They not only observed an increase in eosinophilic inflammation in the Atg7-deficient mice but also associated dysregulation of the prostaglandin D 2 pathway.…”
Section: Eosinophils and Allergic Inflammationmentioning
confidence: 99%
“…In a novel study examining the role of the prostaglandin pathway in chronic rhinosinusitis (CRS), Choi et al 1 deleted the autophagy-related gene Atg7 in the myeloid lineage of mice challenged with a mixture of Aspergillus species protease and ovalbumin to induce CRS. 1 They not only observed an increase in eosinophilic inflammation in the Atg7-deficient mice but also associated dysregulation of the prostaglandin D 2 pathway. Macrophage autophagy and IL-1 played a major role in this process, highlighting a potential new therapeutic approach for CRS.…”
Section: Eosinophils and Allergic Inflammationmentioning
confidence: 99%